The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1080/21655979.2021.1999551
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane protects against cerebral ischemia/reperfusion injury via microrna-30c-5p modulating homeodomain-interacting protein kinase 1

Abstract: Sevoflurane (SEV) has been reported to be an effective neuroprotective agent for cerebral ischemia/reperfusion injury (CIRI). However, the precise molecular mechanisms of Sev preconditioning in CIRI remain largely unknown. Therefore, CIRI model was established via middle cerebral artery occlusion method. SEV was applied before modeling. after successful modeling, lentivirus was injected into the lateral ventricle of the brain. Neurological impairment score was performed in each group, and histopathologic condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…The previous observations substantiate these findings showing that SOX9 deletion in mice imparted a protective effect against transient middle cerebral artery occlusion injury, resulting in improved post-stroke neurological recovery and neuroprotection [73]. From in vitro oxygen-glucose deprivation and reperfusion models, it is evident that miR-30c targets 3 UTR of SOX9 [44], homeodomain-interacting protein kinase 1 (HIPK1) [72], and Rho-associated coiled-coil containing protein kinase 2 (ROCK2) [74] gene, which might attenuate oxidative stress and inflammation. Experimental data revealed that "miR-30c-5p antagomir" enhanced oxidative stress, inflammation, infarct area, and neurological deficits in a transient middle cerebral artery occlusion rat model.…”
Section: Mir-30c In Strokesupporting
confidence: 59%
See 2 more Smart Citations
“…The previous observations substantiate these findings showing that SOX9 deletion in mice imparted a protective effect against transient middle cerebral artery occlusion injury, resulting in improved post-stroke neurological recovery and neuroprotection [73]. From in vitro oxygen-glucose deprivation and reperfusion models, it is evident that miR-30c targets 3 UTR of SOX9 [44], homeodomain-interacting protein kinase 1 (HIPK1) [72], and Rho-associated coiled-coil containing protein kinase 2 (ROCK2) [74] gene, which might attenuate oxidative stress and inflammation. Experimental data revealed that "miR-30c-5p antagomir" enhanced oxidative stress, inflammation, infarct area, and neurological deficits in a transient middle cerebral artery occlusion rat model.…”
Section: Mir-30c In Strokesupporting
confidence: 59%
“…Experimental data revealed that "miR-30c-5p antagomir" enhanced oxidative stress, inflammation, infarct area, and neurological deficits in a transient middle cerebral artery occlusion rat model. These effects were prevented by the upregulation of miR-30c-5p by sevoflurane or flurbiprofen axetil pretreatments [44,72]. MiR-30c-5p attenuates pathological pathways such as mitogen-activated protein kinases by targeting ROCK2 [74], which presents a novel therapeutic target, miR-30c/ROCK2, in the pathogenesis of stroke.…”
Section: Mir-30c In Strokementioning
confidence: 99%
See 1 more Smart Citation
“…Sevoflurane is an effective neuroprotective agent for cerebral I/R injury. 12,13 Sevoflurane treatment has been reported to reduce neurological impairment, cerebral infarction volume, and inflammatory cytokine levels. Sevoflurane has also been shown to reduce neuronal apoptosis and antioxidant stress.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that sevoflurane reduced neurological impairment, cerebral infarction volume, and inflammatory cytokine levels. [10][11][12] At the same time, sevoflurane has been shown to reduce neuronal apoptosis and antioxidant stress. [13][14][15] Sevoflurane plays a protective role in neuronal HIBI by inhibiting apoptosis and necrosis.…”
Section: Introductionmentioning
confidence: 99%